Theories of crowdfunding and token issues: A review - Anton Miglo (Journal of Risk and Financial Management, 2022)
Entrepreneurial, innovative and small- and medium-sized firms experience difficulties with raising funds using traditional debt and equity. Consequently, they are constantly looking for new strategies of financing. The latest inventions are crowdfunding and token issues. In contrast to traditional ways of raising funds these innovations: (1) use modern technology (online transactions, blockchain, etc.) much more actively; (2) are usually quicker in reaching potential investors/funders; (3) use more active network benefits such as, for example, a large number of interactions between investors/funders and between funders and firms. These changes are so significant that some experts list them among the top business inventions of the 21st century. This article provides a review of the growing number of theoretical papers in the areas of crowdfunding and token issues, compares their findings with empirical evidence and discusses directions for future research. The research shows that a large gap exists between the theoretical literature and empirical literature.
Keywords: 650; crowdfunding; entrepreneurial finance; initial coin offerings (ICOs); initial ex-change offerings (IEOs); security token issues (STOs); token issues